An Electrocardiographic Characterization of Left Bundle Branch Area Pacing-Induced Right Ventricular Activation Delay: A Comparison With Native Right Bundle Branch Block - Ozpak, Emine; Demolder, Anthony; Kizilkilic, Sevda; Calle, Simon; Timmermans, Frank; De Pooter, Jan (Frontiers in Cardiovascular Medicine, 2022)
Background: Left bundle branch area pacing (LBBAP) induces delayed RV activation and is thought to be harmless, since the electrocardiographic signature is reminiscent to native RBBB. However, to what extent the delayed RV activation during LBBAP truly resembles that of native RBBB remains unexplored. Methods: This study included patients with incomplete RBBB (iRBBB), complete RBBB (cRBBB) and patients who underwent LBBAP. Global and right ventricular activation times were estimated by QRS duration and R wave peak time in lead V1 (V1RWPT) respectively. Delayed RV activation was further characterized by duration, amplitude and area of the terminal R wave in V1. Results: In patients with LBBAP (n=86), QRS duration (120ms [116;132]) was longer compared to iRBBB patients (n=422): 104ms [98;110]), p<0.001, but shorter compared to cRBBB (n=223): 138ms [130;152], p<0.001. V1RWPT during LBBAP (84ms [72;92]) was longer compared to iRBBB (74ms [68;80], p< 0.001), but shorter than cRBBB (96ms [86;108], p<0.001). LBBAP resulted in V1 R’ durations (42ms [28;55]) comparable to iRBBB (42ms [35;49], p=0.49) but shorter than in cRBBB (81ms [68;91], p<0.001). During LBBAP, the amplitude and area of the V1 R’ wave were more comparable with iRBBB than cRBBB. V1RWPT during LBBAP was determined by baseline conduction disease, but not by LBBAP capture type. Conclusion: LBBAP-induced delayed RV activation electrocardiographically most closely mirrors the delayed RV activation as seen with incomplete rather than complete RBBB.